Analysis of peripapillary vessel density and Bruch’s membrane opening-based neuroretinal rim parameters in glaucoma using OCT and OCT-angiography - Enders, Philip; Longo, Valentina; Adler, Werner; Horstmann, Jens; Schaub, Friederike; Dietlein, Thomas; Cursiefen, Claus; Heindl, Ludwig M. (Eye, 2019)
Purpose: To compare peripapillary vessel density (VD) measured by spectral domain optical coherence tomography angiography (SD-OCT-A) with morphometric parameters assessing the neuroretinal rim based on Bruch’s membrane opening (BMO) by spectral domain optical coherence tomography (SD-OCT) in glaucoma. Methods: In this non-interventional cohort study, 50 eyes of 25 consecutively enrolled patients with diagnosis of glaucoma underwent SD-OCT and SD-OCT-A imaging of the optic nerve head (ONH). BMO minimum rim width (BMO-MRW) and area (BMO-MRA) as well as peripapillary retinal nerve fiber layer (RNFL) thickness were compared to peripapillary VD in the RNFL layer around the ONH. Results: Mean BMO-MRW was 221.46 ± 81.5 µm, mean BMO-MRA was 1.05 ± 0.04 mm2, mean RNFL thickness was 72.46 ± 23.16 µm, and mean VD was 43.8 ± 11.4%. VD was significantly lower when morphometric parameters had lower thickness values (p < 0.01). Correlation coefficients and their 95%- confidence intervals (95%-CI) with VD were r = 0.53 (95%-CI: 0.21–0.77) for BMO-MRW, r = 0.55 (95%-CI: 0.21–0.77) for BMO-MRA, and r = 0.57 (95%-CI: 0.13–0.73) for RNFL thickness. Intra-individual VD in both eyes correlated with r = 0.72 (p < 0.001), mean VD was comparable (p = 0.6). Eyes with high global RNFL thickness (>90 µm) showed less VD variance (σ2 = 48.1) compared to eyes with highly reduced RNFL thickness (<65 µm; σ2 = 82.0). Best corrected visual acuity, perimetric mean defect, and PSD correlated significantly with VD (95%-CI: −0.66 to −0.10, 0.16 to 0.6, and −0.65 to −0.02, respectively). Conclusions: Peripapillary vessel density measured by SD-OCT angiography correlates significantly with Bruch’s membrane opening-based parameters measured by SD-OCT in glaucoma patients.
CRIS-Team Scopus Importer:2019-11-12